ICT Based Activities as Part of Smart Economy in Developing World: Learnt From Indonesia's Home Based Enterprises. (August 2019) - Tyas, W P; Sianturi, O; Riswandha, Y; Sunarti,; Manaf, A; Manullang, OR
Abstract: The study of home industries which place economic activities at home, as part of SMEs, has been explored world widely. When this kind of economic activity in developed countries is more in technology based activities, such as ICT based activities, in developing countries start to have this kind of activities. This research will explore how an ICT based activities affect to support home-based enterprises in Indonesia, with case studies in Magelang Regency and surrounding areas of Rawapening Swamp, Semarang Regency. By using both quantitative and qualitative data, this research aims to a better knowledge on how technologies also part of home-based enterprises, therefore proper responses in policies and programmes can be formulated.